Intrapartum antibiotics for GBS prophylaxis alter colonization patterns in the early infant gut microbiome of low risk infants. Issue 1 (December 2017) - Stearns, Jennifer; Simioni, Julia; Gunn, Elizabeth; McDonald, Helen; Holloway, Alison; Thabane, Lehana; Mousseau, Andrea; Schertzer, Jonathan; Ratcliffe, Elyanne; Rossi, Laura; Surette, Michael; Morrison, Katherine; et al.
Abstract Early life microbial colonization and succession is critically important to healthy development with impacts on metabolic and immunologic processes throughout life. A longitudinal prospective cohort was recruited from midwifery practices to include infants born at full term gestation to women with uncomplicated pregnancies. Here we compare bacterial community succession in infants born vaginally, with no exposure to antibiotics (n = 53), with infants who were exposed to intrapartum antibiotic prophylaxis (IAP) for Group BStreptococcus (GBS; n = 14), and infants born by C-section (n = 7). Molecular profiles of the 16 S rRNA genes indicate that there is a delay in the expansion ofBifidobacterium, which was the dominate infant gut colonizer, over the first 12 weeks and a persistence ofEscherichia when IAP for GBS exposure is present during vaginal labour. Longer duration of IAP exposure increased the magnitude of the effect onBifidobacterium populations, suggesting a longer delay in microbial community maturation. As with prior studies, we found altered gut colonisation following C-section that included a notable lack of Bacteroidetes. This study found that exposure of infants to IAP for GBS during vaginal birth affected aspects of gut microbial ecology that, although dramatic at early time points, disappeared by 12 weeks of age in most infants.